Pengawasan Penertiban Tiang Tumpu Fiber Optic Oleh Satuan Polisi Pamong Praja Kota Pekanbaru - Wahyuni, Siti; Ananda, Fajriani (Yayasan Amanah Nur Aman, 2025)
The unauthorized installation of fiber optic poles in the city of Pekanbaru has had a negative impact on safety, aesthetics, and urban order. Enforcement by the Pekanbaru Municipal Police, which is responsible for addressing these violations, has not been optimal. This study aims to analyze the implementation of enforcement by the Satpol PP in the context of monitoring violations related to the installation of fiber optic support poles. Using a qualitative approach with a phenomenological method, this study identifies four monitoring indicators, as outlined by Jones and George: setting standards and targets, measuring performance, comparing results with these standards, and taking corrective actions. The results show that the establishment of standards and targets is not yet specific, performance measurement is not yet measurable, comparison of results is not systematic, and corrective actions are sporadic. Enforcement remains reactive and dependent on community reports, rather than being based on a structured work plan. The recommendation of this study is the need for a more structured, data-driven, and consistent enforcement system to create equitable public order.